2016
DOI: 10.1159/000448995
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Echocardiographic Assessment of Foramen Ovale Appearance in Fetuses with <smlcap>D</smlcap>-Transposition of the Great Arteries and Impact on Neonatal Outcome

Abstract: Introduction: Neonates with D-transposition of the great arteries (dTGA) may die at birth because of the inadequate intracardiac mixing due to a misdiagnosed restrictive foramen ovale. We reviewed our experience in echocardiographic assessment and perinatal management of fetuses with dTGA searching for new features that may predict the need for urgent balloon atrial septostomy (BAS) immediately after birth. Patients and Methods: We included fetuses diagnosed with dTGA between January 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 27 publications
3
40
1
Order By: Relevance
“…The foramen ovale flap (FOF), which derives primarily from the septum primum, partially covers this interatrial communication. The FOF has been defined as redundant (RFOF), in the context of fetal congenital heart disease (CHD), when it herniates into the left atrium for more than 50% of the left atrial diameter 2,4 . In normal fetal hearts, a RFOF has been reported to occur in roughly one third of the cases with a restrictive FO 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The foramen ovale flap (FOF), which derives primarily from the septum primum, partially covers this interatrial communication. The FOF has been defined as redundant (RFOF), in the context of fetal congenital heart disease (CHD), when it herniates into the left atrium for more than 50% of the left atrial diameter 2,4 . In normal fetal hearts, a RFOF has been reported to occur in roughly one third of the cases with a restrictive FO 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Three other retrospective case-series studies that examined possible predictors of urgent BAS using different fetal echocardiography markers in neonates with TGA were identified. Tuo et al 2 demonstrated restrictive FO or hypermobile or redundant septum primum was significantly associated with the need for urgent BAS. Punn and Silverman3 also examined the morphology and function of FO, and ductal size and shunting pattern.…”
Section: Commentarymentioning
confidence: 99%
“…The following terms were used: exp ‘INFANT, NEWBORN’/OR (newborn * OR neonates*) AND exp ‘HEART DETECTS, CONGENITAL’/OR (congenital heart AND (defect* OR malformation*)) AND exp ‘ULTRASONOGRAPY, PRENATAL’/OR ((prenatal OR antenatal) AND (ultrasonography OR ultrasound OR scan)) OR (echocardiogram OR echocardiograph*, OR ‘cardiac echo’) AND exp FETUS/OR exp ‘FETAL RESEARCH’/OR ((fetal OR foetal OR fetus OR fetus OR prenatal OR antenatal) AND echocardiog*) AND (‘Balloon atrial septostomy’ OR atrial septostomy), OR Balloon atrial septostomy OR atrioseptostomy). In total, 31 publications were identified, in which 4 studies were relevant on further review 1–4. All 4 studies included newborns with an antenatal diagnosis of TGA.…”
Section: Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…The case group was selected from cases in which the FO valve had a shape or motion abnormality. The FO valve was diagnosed as a shape abnormality when it appeared to be either aneurysmal or hypermobile as previously described [11][12][13]; or motion abnormality, when it appeared to be thick and flat without a "flapping" motion normally seen in the uterus [14,15]. The cases diagnosed with congenital heart diseases or with no clear images were excluded.…”
Section: Study Populationmentioning
confidence: 99%